Retrospective analysis of prescriptions in the management of lepra reactions: Results of a single center study from tertiary hospital in Maharashtra - Kulkarni, Madhuri; Patil, Anant; Aathawale, Siddharth (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To examine pattern of lepra reaction andmedicines used in the treatment of lepra reactions in a tertiary hospital. Material methods: In this retrospective study, prescriptions of patients treated for the lepra reactions were reviewed to find out prevalence of type 1 and type 2 reactions and medicines used in the treatment of lepra reactions. Results:A total of66 patients (male 59.1%; female 40.9%) with mean age of 36.6 (+13.1) years were included in the study. Multibacillary leprosy was present in 93.7% patients.Â A total of 39 (60%) patients had type 2 reaction whereas 26 (40%) had type 1 reaction. Mean number of medicines per patients was 7.5. Prednisolone was used in 62 (93.9%) patients with mean duration of 33.32 (+33.2) days whereas chloroquine was used in 52 (78.8%) patients for 36.6 (+27.9) days. Thalidomide was used in 25 (37.9%) patients. Analgesic and anti-inflammatory and anti-acidity drugs were used in 63 (95.4%) patients each whereas paracetamol was given to 41 (62.1%) patients. Antihistamine, antimicrobial agent and vitamins were given to 27 (40.9%), 27 (40.9%) and 35 (53.0%) patients respectively. Conclusion:Lepra 2 reaction is more common than lepra 1 reaction.Â Prednisolone and chloroquine are the two most commonly used medicines in the treatment of lepra reaction. Similarly, thalidomide, older drug has emerged as common treatment for lepra reaction.